Impact of Front Line Demonstration on Production and Productivity of Niger [Guizotia abyssinica (L.f.) Cass] in Eastern Ghat High Land zone of Odisha - Dalei, B. B.; Meena, M. K.; Nayak, L.; Behera, B. R.; Sahoo, B. B.; Senapati, N. (International Journal of Bio-resource and Stress Management, 2023)
Niger is an edible oilseed crop of tribal farmers of Eastern Ghat High Land zone of Odisha. It supplements to the socio-economic condition and fulfills the requirement of cooking oil of the Indian tribal community. The production and productivity of Niger crop continues to be quite low due to low levels of management in crop production, cultivation in poor marginal lands and repeated use of local cultivars. The yield of Niger can be increased by demonstrating the improved agronomic package of practices viz. timely sowing of the crop, proper nutrient management, weed management and need based plant protection measures at the farmer’s field under the keen supervision of concern scientists working in the operational area. Keeping in view, the front line demonstration was conducted on Niger crop, under All India Coordinated Research Project on Niger operating at Regional Research and Technology Transfer Station (OUAT), Semiliguda in farmer’s field for a consecutive year from 2010–11 to 2012–13. The increase in seed yield of 149%, 124% and 123% with cost benefit ratio of 1.28, 1.61 and 1.38 was obtained from front line demonstration on whole package, improved variety i.e. Utkal Niger-150 and recommended dose of fertilizer 40:40:20 of N:P:K over farmers practices respectively. It can be concluded that FLD programme on niger effectively increase the production and productivity in the specific region of Odisha.